Systematic approach to the development of methods of prevention of gastro-intestinal diseases in newborn calves - O. A. Burova; A. A. Blokhin (Аграрная наука Евро-Северо-Востока, 2017)
The main condition for the prevention of diseases in calves in early postnatal period is the formation of an optimal immunological status of cows-mothers, provision of colostral immunity and colonization resistance of mucous membranes in newborn calves. Methods of prevention of gastro-intestinal diseases should be based on the key provisions on the system “mother-fetus-newborn”. Our methods includes improving the immune status of different age groups of cattle population united in the system “mother-fetus-newborn” and consists of two stages. In the first stage pregnant cows three months before calving are given the remedy “Immoveton-Ks” at a dose 0f 52.5 mg/kg BW. Then 2 months before calving cows are immunized with vaccine “Hiprobovis-4” at a dose of 3 ml with a booster after 21-30 days. In the second stage newborn calves are given combination of some remedies: “Immoveton-Ks” intramuscularly or subcutaneously at a dose of 52.5 mg /kg BW once daily on day 1, 2 and 7 of life; fermented milk product “EM-Kurunga” orally at a dose of 150 ml from the second day of life 3 times a day for 10 days; Multivitamin + Minerals intramuscularly at a single dose of 1.5 ml on day 8 of life. It is established that immunization with the vaccine “Hiprobovis-4” against the background of correction of the immune status using “Immoveton-Ks” provides for the production of the greatest quantity of specific antibodies. This indicates pronounced stimulating effects of immunomodulator “Immoveton-Ks” on the formation of post-vaccination immunity. Preventive effectiveness of the proposed method on farms with high prevalence of gastrointestinal diseases of calves was 90.5%, the safety - 98.9%, average daily weight gain - 840g.